Pengaruh Tradisi Mappadekko Pada Hasil Panen Masyarakat Di Desa Walenreng Kabupaten Bone - Muh. Farhi; Ais Magfirah Maulani; Nur Fauziah Ikhwan; Ahmad Kurniawan; Sendi Safitri; Kristiawati Kristiawati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
There is a perception from the community towards the Mappadekko tradition which is believed to have an influence on the harvests of the Walenreng Village farming community. The problems in the research are considered important to  be carried out in order to find answers to the beliefs held by conducting a study regarding "The Influence of the Mappadekko Tradition on Community Harvest Results in Walenreng Village, Bone Regency. The aim of this research is to determine the influence of  the  Mappadekko  tradition  on  community harvests in Walenreng Village, Cina District, Bone Regency. This type of research uses ethnography. The instrument used was an interview guide. The data analysis techniques used are data condensation, data presentation, and drawing conclusions. The results of this research show that this research program has been implemented well, namely that the majority of the planned research activities have been carried out well  with  good  results  achieved.  This  research produced six pieces of information, namely what the Mappadekko tradition is, the community's response to the Mappadekko tradition, when the Mappadekko tradition was carried out, the advantages and disadvantages of the Mappadekko tradition, incidents when the Mappadekko tradition was not carried out, and the influence ofthe Mappadekko tradition on the community's harvest.